Beneath the surface: A 25-year review of soil monitoring in the U.S. Forest Inventory and Analysis program - Melissa A. Pastore; Ashley K. Lang; John D. Shaw; Sean M.P. Cahoon; Hayley Peter-Contesse; Suzanne M. Owen; Randall S. Morin; Jonathan A. Knott; Grant M. Domke; Belinda Esham; Erin M. Berryman (Forest Ecology and Management, 2025)

Mapping Oak (Quercus spp.) Regeneration Potential Within the Nantahala National Forest - Quentin Ikuta; John Zobel; Joseph Knight; Jonathan Knott; Brandon Stephens; Nicholas J. Partington; Marcella A. Windmuller-Campione (Journal of Forestry, 2025)
Forest mesophication threatens the regeneration and potential future perpetuation of oak ( Quercus spp.) forests throughout southern Appalachia and eastern United States (US). We explored methods to produce stand-scale oak site suitability maps, within the Nantahala National Forest in North Carolina, which can be used to prioritize site-specific treatments to allow for oak regeneration and recruitment using silvicultural strategies to reduce forest mesophication. To establish initial conditions, USDA Forest Service common stand exam quick plot protocol was followed, and plot data collected from June through August 2023 at 180 sample points within 15 stands totaling 500 acres. Collection of seedling height class data was important for showing a gap in regeneration, between the number of small seedlings (~ 1 ft) (1038 stems) and large seedlings (> 4.5 ft) (301 stems). Two popular site suitability modeling techniques, Maximum Entropy (MaxEnt) and Random Forest, were run for five common oak species with seven predictor variables including available water capacity, elevation, eastness, ecozone, northness, soil acidity, and soil type. MaxEnt models consistently outperformed Random Forest models with the most important variables including ecozone, soil acidity, and soil type. The maps highlight locations that can be prioritized for silvicultural treatments that target regeneration and recruitment of oaks to combat or reverse forest mesophication.

Leveraging Remote Sensing and Theory to Predict Tree Size Abundance Distributions Across Space - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; J. Marcos Rodriguez; Ben Weinstein; David A. Orwig; Sydne Record (Global Ecology and Biogeography, 2025)
Background Remote sensing (RS) technologies provide unprecedented opportunities to assess forest structure at broad spatial scales. Light detection and ranging (LiDAR) is a powerful tool that offers detailed vertical information, but its consistent high‐resolution coverage can be limited across vast areas and quantifying understory vegetation remains challenging due to occlusion. Conversely, while high‐resolution RGB imagery is more accessible and valuable for large‐scale analyses, it comes with higher uncertainty and only captures canopy‐level information. Integrating RGB data with ecological theory and existing LiDAR‐derived products (e.g., canopy height models, CHM) allows us to enhance predictions and broaden the applicability of forest size structure mapping from the understory to the canopy, particularly through tree size–abundance relationships. Theory Tree size and abundance generally follow known distributions, where smaller trees are exponentially more common than larger trees. This pattern emerges from fundamental ecological constraints, including volume packing, metabolic scaling and light competition, which collectively govern forest self‐organisation across spatial scales. Proposed Approach We present a workflow that integrates size‐abundance scaling theory with RGB data and CHMs to improve predictions of forest structure. By estimating tree size distributions from RGB imagery, we extend the applicability of ecological scaling models to broader spatial scales and offer an approach that complements traditional methods. Assessment We apply this approach to forest monitoring networks, including NEON and ForestGEO, to assess its accuracy and generalisability across a range of forests (e.g., subtropical pine, boreal, low and dry, tall and dense) in North America. Our results show that RGB‐based estimates can successfully recover size‐abundance distributions from the understory to the canopy. Future Directions Further refinement of our approach could enhance predictions by incorporating species classifications from hyperspectral data and using more spatially or taxonomically specific allometric equations. These additions would enable more precise scaling of tree diameter from remote sensing data.

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

Shifting Forests and Carbon: Linking Community Composition and Aboveground Carbon Attributes - Jonathan Knott; Grant Domke; Christopher Woodall; Brian Walters; Michael Jenkins; Songlin Fei (Ecosystems, 2023)

Phenological response to climate variation in a northern red oak plantation: Links to survival and productivity - Jonathan A. Knott; Liang Liang; Jeffrey S. Dukes; Robert K. Swihart; Songlin Fei (Ecology, 2023)
In a changing climate, the future survival and productivity of species rely on individual populations to respond to shifting environmental conditions. Many tree species, including northern red oak ( Quercus rubra ), exhibit phenotypic plasticity, the ability to respond to changes in environmental conditions at within‐generation time scales, through varying traits such as leaf phenology. Phenotypic plasticity of phenology may vary among populations within a species' range, and it is unclear if the range of plasticity is adequate to promote fitness. Here, we used a 58‐year‐old common garden to test whether northern red oak populations differed in phenological sensitivity to changes in temperature and whether differences in phenological sensitivity were associated with differences in productivity and survival (proxies of fitness). We recorded 8 years of spring leaf emergence and autumn leaf coloration and loss in 28 distinct populations from across the species' full range. Across the 28 populations, spring leaf out consistently advanced in warmer years, but fall phenology was less responsive to changes in temperature. Southern, warm‐adapted populations had larger shifts in phenology in response to springtime warming but had lower long‐term survival. Moreover, higher phenological sensitivity to spring warming was not strongly linked to increased productivity. Instead, fitness was more closely linked to latitudinal gradients. Although springtime phenological sensitivity to climate change is common across northern red oak populations, responses of productivity and survival, which could determine longer‐term trajectories of species abundance, are more variable across the species' range.

Community‐level responses to climate change in forests of the eastern United States - Jonathan A. Knott; Michael A. Jenkins; Christopher M. Oswalt; Songlin Fei (Global Ecology and Biogeography, 2020)
Aim Climate change has impacted forest ecosystems, leading to species‐level tree migration. However, the impacts of climate change on forest communities are mostly unknown. Here, we assess changes to forest communities at three scales: within‐community changes in species composition, individual community spatial shifts and changes across all communities. Location Eastern USA. Major taxa studied Forest tree species. Methods Using a region‐wide forest inventory dataset from the United States Department of Agriculture Forest Service's Forest Inventory and Analysis Program with > 70,000 plots, we identified forest communities using the latent Dirichlet allocation method. We analysed changes in species composition within communities and assessed community‐level spatial shifts over the last three decades to quantify the responses of individual communities to climate change. We used the distribution of forest communities across climate conditions to predict where communities could migrate to during the study period and compared climate‐predicted shifts with observed community shifts. Changes across all communities were modelled as a function of climatic and non‐climatic variables using generalized linear mixed‐effects models. Results We identified 12 regional forest communities of the eastern USA, which varied in their stability of species composition over the study period. All communities experienced relatively short yet significant shifts in their spatial distribution (median = 8.0 km/decade). Historical climate and changes in seasonal temperature variability were the best predictors of change across all communities. However, the distance and direction of individual community migration were poorly predicted by climate change, and the observed direction was often the opposite of the predicted direction. Main conclusions Forest communities shifted their distributions over the last three decades, but climate change outpaced the rate of community migration. Continued lags between climate change and forest community responses and the lack of migration in the direction predicted by climate change might lead to the inability of forests to keep up with changing climate.

A global analysis of elevational distribution of non‐native versus native plants - Qinfeng Guo; Songlin Fei; Zehao Shen; Basil V. Iannone; Jonathan Knott; Steven L. Chown (Journal of Biogeography, 2018)
Aim Much is known about the elevational diversity patterns of native species and about the mechanisms that drive these patterns. A similar level of understanding is needed for non‐native species. Using published data, we examine elevational diversity patterns of non‐native plants and compare the resulting patterns with those observed for native plants. Location Global. Methods We compiled data from 65 case studies on elevational diversity patterns of non‐native plants around the world (including 32 cases in which both non‐native and native plants were sampled). We compared the elevational distributions (upper and lower limits, and extents) and diversity patterns of non‐native and native species. Results Compared to native plant species, the elevational diversity patterns of non‐native plant species were more negative (47% vs. 13%) and less unimodal (44% vs. 84%). That is, non‐native species richness tended to be highest at lower elevations, whereas native species richness peaked at mid‐elevations. In cases where species richness for both non‐native and native species on the same mountains showed unimodal patterns in relation to elevation, maximum values in species richness occurred at lower elevations for non‐native species. Main conclusions At present levels of invasion, non‐native and native species show different patterns in both distribution and diversity along elevational gradients worldwide. However, our observations constitute a snapshot of ongoing, long‐term invasion processes. As non‐native species typically show strong associations with human activities, future changes in human population (e.g. growth and migration), land use and climate change may promote upward spread of non‐native species and may thus increase risks of impact on native species and communities.